FROM CHAOS TO CHAOS: SOUTH YEMEN 50 YEARS AFTER THE BRITISH DEPARTURE. Issue 3 (3rd July 2017) - Brehony, Noel
Abstract : Fifty years after the British departure the future of South Arabia or South Yemen is just as uncertain as it was on 30 November 1967, when the People's Republic of South Yemen (PRSY) came into existence. The old order was swept away in the revolutionary tide of the mid- 20 th century to be replaced by a Marxist state. Yet, within less than 23 years the new order was undermined by unresolved issues inherited from South Arabia and led to an ill-prepared union with the Yemen Arab Republic (YAR) in 1990. Today, after over two and half years of war, Yemen is fragmenting and one outcome might be the return of a southern state which will have to confront the same unresolved issues. Are southerners Yemenis or South Yemenis? Can institutions be created to overcome tribal and regional differences with the South? Can a viable economy be created in a country with so few natural resources? This article provides a history of the region and the conflicts of the last 50 years, along with a consideration of the present situation and a discussion of the enduring issues.